Temporal detection and phylogenetic assessment of SARS-CoV-2 in municipal wastewater - Nemudryi, Artem (medRxiv, 2020)
SARS-CoV-2 has recently been detected in feces, which indicates that wastewater may be used to monitor viral prevalence in the community. Here we use RT-qPCR to monitor wastewater for SARS-CoV-2 RNA over a 52-day time course. We show that changes in SARS-CoV-2 RNA concentrations correlate with local COVID-19 epidemiological data (R(2)=0.9), though detection in wastewater trails symptom onset dates by 5–8 days. We determine a near complete (98.5%) SARS-CoV-2 genome sequence from the wastewater and use phylogenic analysis to infer viral ancestry. Collectively, this work demonstrates how wastewater can be used as a proxy to monitor viral prevalence in the community and how genome sequencing can be used for high-resolution genotyping of the predominant strains circulating in a community.